Problematic alcohol use in the family and adolescents' stress-related complaints. (20th October 2021) - Brolin Låftman, S; Magnusson, C; Olsson, G; Svensson, J; Wahlström, J; Modin, B
Abstract: Background: A non-negligible proportion of children grow up in families where problematic alcohol use is present. From a resilience perspective and for the implementation of effective interventions, it is relevant to examine to what extent favourable conditions in other contexts may buffer against such family adversities. The aim of the current study was to examine the relationship between problematic familial alcohol use and offspring stress-related complaints. Another aim was to explore whether teacher ratings of the school's degree of student focus can buffer against negative health consequences of problem drinking at home. Methods: Data were drawn from four cross-sectional surveys conducted in 2014 and in 2016 among 8, 728 students (∼15-16 years) and 2, 024 teachers in 147 Stockholm senior-level school units, with linked school-level register information. Stress-related complaints were measured from students' reports on the weekly co-occurrence of stomach-ache and headache. Teachers' ratings of the school's student focus were measured by an index based on four items which was aggregated to the school level. Student-level sociodemographic characteristics were included as control variables along with the schools' composition and student-teacher ratio. Two-level binary logistic regression analyses were performed. Results: Problematic familial alcohol use was associated with an increased likelihood of stress-related complaints among students (OR 1.74, 95% CI 1.44-2.10). The cross-level interaction revealed that this association was weaker among students in schools with higher levels of student focus. Conclusions: The study showed that the association between problematic familial alcohol use and students' stress-related complaints was less pronounced in schools with higher teacher ratings of student focus. This finding indicates that favourable conditions in schools can buffer against problematic conditions in the family, thus serving a compensatory role. Key messages: Students reporting problematic familial alcohol use were more likely to suffer from stress-related complaints. High teacher ratings of the school's student focus buffered against the association between problematic familial alcohol use and stress-related complaints.